Analysis of Pollutant Distribution Due to Forest Fires in Ketapang Regency in 2015 Using The WRF-Chem Model - Yani, Elyda; Ihwan, Andi; Ardianto, Randy; Adriat, Riza; Jumarang, Muhammad Ishak (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
A forest fire occurred on September 9, 2015, resulting in 616 hotspots distributed across several regencies in West Kalimantan, 442 of which were in Ketapang Regency. This study aims to analyze the spatial and temporal distribution of pollutants caused by forest fires in Ketapang Regency in 2015 using the Weather Research and Forecasting with Chemistry (WRF-Chem) model. The data used to run the model includes the Final Global Data Assimilation System (FNL) dataset, the Emission Database for Global Atmospheric Research (EDGAR), and The Fire Inventory from NCAR (FINN), which serve as input and emission source data. The highest concentrations of pollutants, which are PM2.5 and PM10 at 30 µg/m³ each and CO at 342.9 µg/m³, were observed in the southern part of Kalimantan, which is the main source of the forest fires. These pollutants subsequently dispersed toward the northern part of Kalimantan. During the fire events, pollutants were transported to the upper atmosphere from morning to noon but accumulated near the surface at night. This pattern was influenced by meteorological conditions, including wind speed and direction, surface pressure, and air temperature. During forest fires, pollutants are emitted into the atmosphere from morning to afternoon, and accumulate near the surface during the night. This pattern was influenced by meteorological factors, including wind speed and direction, surface pressure, and air temperature.